TMI-1, TNF-α-Converting Enzyme Inhibitor, Protects Against Paclitaxel-Induced Neurotoxicity in the DRG Neuronal Cells In Vitro - Kim, Yesul; Jung, Young-Hoon; Park, Seung-Bin; Kim, Heekee; Kwon, Jae-young; Kim, Hae-kyu; Lee, Hyeon-Jeong; Jeon, Soeun; Kim, Eunsoo (Frontiers in Pharmacology, 2022)
Background: Chemotherapy-induced peripheral neuropathy (CIPN) negatively impacts cancer survivors’ quality of life and is challenging to treat with existing drugs for neuropathic pain. TNF-α is known to potentiate TRPV1 activity, which contributes to CIPN. Here, we assessed the role of TMI-1, a TNF-α-converting enzyme inhibitor, in paclitaxel (PAC)-induced neurotoxicity in dorsal root ganglion (DRG) cells. Materials and Methods: Immortalized DRG neuronal 50B11 cells were cultured and treated with PAC or PAC with TMI-1 following neuronal differentiation. Cell viability, analysis of neurite growth, immunofluorescence, calcium flow cytometry, western blotting, quantitative RT-PCR, and cytokine quantitation by ELISA were performed to determine the role of TMI-1 in neurotoxicity in neuronal cells. Results: PAC administration decreased the length of neurites and upregulated the expression of TRPV1 in 50B11 cells. TMI-1 administration showed a protective effect by suppressing inflammatory signaling, and secretion of TNF-α. Conclusions: TMI-1 partially protects against paclitaxel-induced neurotoxicity by reversing the upregulation of TRPV1 and decreasing levels of inflammatory cytokines, including TNF-α, IL-1β, and IL-6 in neuronal cells.